A Study Of Diffusion And Adoption Of E-Innovation Services In Malaysia - Hj. Mohideen, Hanizah (2004)
This research looks into the diffusion and adoption of E-Innovations, namely , Internet Banking, E-Finance, Online Hotel Reservation System and Telemedicine System. Hence the objectives of this study are to evaluate consumers' usage, perception and also problems faced during the use of these services. It is expected that the results of this study will be beneficial to bankers, finance institutions, hotels, hospitals and clinics.